2015
DOI: 10.18632/oncotarget.6617
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan stimulates pancreatic cancer cell motility

Abstract: Hyaluronan (HA) accumulates in pancreatic ductal adenocarcinoma (PDAC), but functional significance of HA in the aggressive phenotype remains unknown. We used different models to investigate the effect of HA on PDAC cell motility by wound healing and transwell migration assay. Changes in cell motility were examined in 8 PDAC cell lines in response to inhibition of HA production by treatment with 4-methylumbelliferone (4-MU) and to promotion by treatment with 12-O-tetradecanoyl-phorbol-13-acetate (TPA) or by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 41 publications
3
50
0
1
Order By: Relevance
“…We also showed that direct addition of LMW‐HA (25–75 kDa) to cultured PDAC cells increased their migration more robustly than HMW‐HA (400–600 kDa) (Fig. ) . Thus, the effects of HA on cell behavior may depend on its size and cell type; however, the mechanism underlying these different effects of HA is not clearly understood.…”
Section: Role Of Ha In Initiation and Progression Of Human Cancersmentioning
confidence: 88%
“…We also showed that direct addition of LMW‐HA (25–75 kDa) to cultured PDAC cells increased their migration more robustly than HMW‐HA (400–600 kDa) (Fig. ) . Thus, the effects of HA on cell behavior may depend on its size and cell type; however, the mechanism underlying these different effects of HA is not clearly understood.…”
Section: Role Of Ha In Initiation and Progression Of Human Cancersmentioning
confidence: 88%
“…In particular, LMW-HA, rather than HMW-HA, is more likely to promote cancer growth and metastasis [8]. We also demonstrated that direct addition of LMW-HA to cultured PDAC cells increased their migration more robustly than HMW-HA [9]. Because HA is degraded by HYALs, accelerated HYAL activity is associated with aggressive tumor progression [3].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, low-molecular-weight- (LMW-) HA or small HA fragments, rather than HMW-HA, have been suggested to be essential for cancer progression in terms of invasion and metastasis [8]. We also reported LMW-HA stimulated PDAC cell migration [9]. Accumulating evidence suggests that HYAL has a critical role in tumor progression.…”
Section: Introductionmentioning
confidence: 86%
“…Interestingly, low-molecular-weight HA (LMW-HA) or small HA fragments, rather than high-molecular-weight HA (HMW-HA), has been suggested to be essential for cancer progression in terms of invasion and metastasis [9, 10]. We also show that LMW-HA stimulates motility of PDAC cells [11]. HA, a large linear glycosaminoglycan of up to 10 6 -10 7 Da in its naïve form, is produced by HA-synthesizing enzymes (HASs) and degraded into smaller fragments by hyaluronidases (HYALs).…”
Section: Introductionmentioning
confidence: 90%